Co-creation of a pedagogical space to support qualitative inquiry: An advanced qualitative collective. (March 2017) - Abboud, Sarah; Kim, Su Kyung; Jacoby, Sara; Mooney-Doyle, Kim; Waite, Terease; Froh, Elizabeth; Sefcik, Justine S.; Kim, Hyejin; Sowicz, Timothy Joseph; Kelly, Terri-Ann; Kagan, Sarah
Abstract: Background: Situated in a research-intensive School of Nursing, the Advanced Qualitative Collective (AQC) provides an innovative educational forum for the study of qualitative research by doctoral and postdoctoral scholars. This long-standing collective is guided by a faculty facilitator using a collaborative co-learning approach to address individual and group needs, from the conception of research projects through dissemination of completed qualitative research. This article describes the dynamics of the AQC and the ways a co-created pedagogical entity supports professional development among its diverse members. The informal, participatory style, and dynamic content used by the AQC resists a course structure typical of doctoral education in health sciences, and promotes engagement and self-direction. The AQC provides opportunities for members to examine theoretical frameworks and methodologies rarely addressed within a positivism-dominant learning environment while simultaneously serving as an alternative exemplar for the pedagogy of research. Highlights: The AQC is a collective space for co-teaching and co-learning qualitative research. The AQC provides educational and research benefits to junior scholars through its yearlong diverse functions. The AQC can be a model for other pedagogical environments. The AQC is an example of a non-proscriptive, sustainable student-centered pedagogical approach. The AQC can be a model for other pedagogical environments.